Amino acids as biomimetic crystallization agents for the synthesis of ZIF-8 particles. Issue 23 (29th February 2016) - Liang, Kang; Ricco, Raffaele; Doherty, Cara M.; Styles, Mark J.; Falcaro, Paolo
Abstract : Biomimetic mineralization of metal–organic frameworks (MOFs) exploits the use of biomolecules to control MOF crystallization processes. Abstract : Biomimetic mineralization of metal–organic frameworks (MOFs) exploits the use of biomolecules to control MOF crystallization processes. Here, we investigate 20 natural amino acids as biomimetic crystallization agents for the synthesis of ZIF-8 particles in aqueous solution. The morphology, size, and particle number of resultant MOF crystals were strongly dependent on the chemical nature of amino acid side chains that match closely the four classes of amino acids: nonpolar, polar neutral, polar negative and polar positive.